TOPAZITE AND ONGONITE DIKES OF THE UTULIK BELT, SOUTHERN BAIKAL REGION - Dergachev V.B. (My University, 1990)
Topaz-rich ongonite varieties given the name of topazites and picnitites have been discovered in recent years. The dikes of the Utulik belt are well known for the high fluorine content of their rocks, which is the result of abundant topaz, the presence of rock-forming cryolite, alumofluorides and fluorite. The geochemical properties of the topazite and ongonite of the Utulik belt are very high concentrations of fluorine and tin (dozens of times the clarkes for granite, as given by Vinogradov. The concentrations of these elements also constitute the principal difference between the topazite and ongonite. Our topazite and ongonite also have low concentrations of Zr, La, Sr, Ba, V, Ti and Mn and high concentrations of Ta (7 to 9 times the clarke for granite), but the topazite is lower in such rare elements as Li, Rb, Y, Yb, Be and Ga than the ongonite. Our investigations of topazite enable us to predict the existence of new types of igneous ores, particularly of the tin-tantalum type.